Seizures in children with neurofibromatosis type 1: is neurofibromatosis type 1 enough? - Claudia Santoro; Pia Bernardo; Antonietta Coppola; Umberto Pugliese; Mario Cirillo; Teresa Giugliano; Giulio Piluso; Giuseppe Cinalli; Salvatore Striano; Carmela Bravaccio; Silverio Perrotta (BMC, 2018)
Abstract Background Neurofibromatosis type 1 (NF1) is related to a generally increased prevalence of seizures. The mechanism underlying the increased predisposition to seizures has not been fully elucidated. The aim of the study was to evaluate the role of NF1 in seizures pathogenesis in a cohort of children with NF1 and seizures. Methods The medical records of 437 children (0-18 years old) with NF1 were reviewed. All children with at least one afebrile seizure were included. Demographic, clinical, neurological, NF1 mutation status, and EEG data were collected along with brain magnetic resonance imaging. Depending on etiology, structural seizures have been identified and were further classified as NF1 related or not. Results Nineteen patients (4.3%; 13 males) were included. NF1 was inherited in 7 (37.5%), with 3 maternal forms. Ten children with structural seizures were identified. Seven forms were identified someway related to NF1, two of which were associated to 17q11.2 microdeletion and hypoxic-ischemic encephalopathy. Any brain lesion that could explain seizures was found in nine patients, two third of these patients had a familiar history of epilepsy. Conclusions Our results suggest seizures are more frequent in NF1 children (4.3%) than in general pediatric population (0.3-0.5%) and that are someway related to NF1 in half of patients. Facing seizures in NF1, the clinician should first exclude brain tumors but also other, and rarer NF1-related scenarios, such as hydrocephalous and vasculopathies. Children with non-structural seizures frequently had a family history of epilepsy, raising questions about the pathogenic role of NF1. They should be approached as for the general population.